CLO Performance - CORDELL, LARRY; ROBERTS, MICHAEL R.; SCHWERT, MICHAEL (Journal of Finance, 2023)
ABSTRACT We study the performance of collateralized loan obligations (CLOs) to understand the market imperfections giving rise to these vehicles and their corresponding economic costs. CLO equity tranches earn positive abnormal returns from the risk‐adjusted price differential between leveraged loans and CLO debt tranches. Debt tranches offer higher returns than similarly rated corporate bonds, making them attractive to banks and insurers that face risk‐based capital requirements. Temporal variation in equity performance highlights the resilience of CLOs to market volatility due to their closed‐end structure, long‐term funding, and embedded options to reinvest principal proceeds.